2020
DOI: 10.1039/c9np00058e
|View full text |Cite
|
Sign up to set email alerts
|

Metal binding ability of microbial natural metal chelators and potential applications

Abstract: Metallophores can chelate many different metal and metalloid ions next to iron, make them valuable for many applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 216 publications
2
28
0
Order By: Relevance
“…Siderophores (greek: sidero = iron; phore = carrier) are secondary metabolites produced by many organisms (plant, bacteria, and fungi) to sequester iron in a physiological context (Kem and Butler 2015;Carroll and Moore 2018;Hofmann et al 2020). Often stress, such as iron limitation or ecological pressure, leads to a response of producing and secreting secondary metabolites.…”
Section: Nmos Involved In Siderophore Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…Siderophores (greek: sidero = iron; phore = carrier) are secondary metabolites produced by many organisms (plant, bacteria, and fungi) to sequester iron in a physiological context (Kem and Butler 2015;Carroll and Moore 2018;Hofmann et al 2020). Often stress, such as iron limitation or ecological pressure, leads to a response of producing and secreting secondary metabolites.…”
Section: Nmos Involved In Siderophore Biosynthesismentioning
confidence: 99%
“…The diverse nature of siderophores and their structural as well as functional elements provide access towards many applications, as has been extensively reviewed (Saha et al 2016;Su et al 2018;Albelda-Berenguer et al 2019;Řezanka et al 2019;Hofmann et al 2020) and will not be discussed in detail here. a b c Fig.…”
Section: Nmos Involved In Siderophore Biosynthesismentioning
confidence: 99%
“…Extracellular metal sequestration and intracellular metal accumulation also provide resistance for microorganisms dealing with high metal concentrations. Extracellular sequestration involves the immobilization of metal ions outside of the cell by interaction with metal chelators [18] or extracellular polymeric substances (EPS) [1]. EPS adsorb toxic metals directly or facilitate reactions involving the products of energy-related metabolisms (e.g., sulfate reduction produces H 2 S to form metal sulfides, or Fe(II) oxidation produces Fe(III) minerals that sorb or incorporate metals) [1].…”
Section: Introductionmentioning
confidence: 99%
“…This study also revealed that both acinetobactins are versatile metal chelators ( Fig. 4 ), not specific to iron, and the physiological relevance of this property was also of interest ( 53 ). However, ICP-OES/MS-based metal sequestration assays with calprotectin ( Fig.…”
Section: Discussionmentioning
confidence: 70%